2000
DOI: 10.1115/1.1342159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Mooring Line Loading Using Large and Small-Scale Models

Abstract: For catenary mooring lines, the relationship between excursion of the point of suspension and the length of suspended line is highly nonlinear. If the point of suspension is then set in motion, the velocity of the line resulting from a change in catenary profile induces additional nonlinear hydrodynamic loading components. The sensitivity of the mooring line to initial and oscillatory conditions results in a complicated tension history at the point of suspension, with line tensions possibly greatly exceeding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Vibrations of one-dimensional systems (i.e., systems with cross-sectional dimension much smaller than their length) suspended under the influence of a downward force have long been of interest in the context of such applications as beams, cables supporting suspension bridges, and ship moorings. Such systems display a wide range of behavior, depending on the amount of slack present in the system, the downward force, and the aspect ratio. Previous studies, which have largely been analytical, have been restricted to certain limiting cases of these parameters.…”
mentioning
confidence: 99%
“…Vibrations of one-dimensional systems (i.e., systems with cross-sectional dimension much smaller than their length) suspended under the influence of a downward force have long been of interest in the context of such applications as beams, cables supporting suspension bridges, and ship moorings. Such systems display a wide range of behavior, depending on the amount of slack present in the system, the downward force, and the aspect ratio. Previous studies, which have largely been analytical, have been restricted to certain limiting cases of these parameters.…”
mentioning
confidence: 99%
“…Thomas and Hearn [ 22 ] indicated that the out-of-plane seabed friction can be negligible and that in-plane effects can influence the peak dynamic tension. Kitney and Brown [ 23 ] presented two different scale experiments to validate the results of other scholars. Qiao and Ou [ 24 ] calculated the hydrodynamic drag damping of single-component mooring line and obtained linearized damping coefficients.…”
Section: Introductionmentioning
confidence: 87%
“…The exhaustion of these fields and the continuous demand for hydrocarbon products has attracted offshore industry experts to explore and produce from fields located in deeper waters. These floating drilling/production systems are moored or tethered to the seabed via TCs [1]. For stationkeeping seabed operating vehicles, continuous human presence in the loop necessitates the utilization of TCs.…”
Section: Introductionmentioning
confidence: 99%
“…TC analysis is a challenging task due to the difficulty in modeling the hydrodynamic forces, which in turn depend on the prevailing physical conditions. Hence, there is a need for a reliable and efficient solution technique for determining the cable profile and tensions [1,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%